Effectiveness of first line therapy for Helicobacter pylori infection in children and adolescents: A multicenter study in the United Arab Emirates - Eman Al Atrash; Amer Azzaz; Antoine AbdelMassih; Amina Bakro; Farah Al-Marzooq (PLoS ONE, 2025)
Globally, gastric infection with Helicobacter pylori has a high prevalence. Bacterial eradication is crucial to prevent long-term complications such as gastric cancer. There is a standard recommended first-line therapy with a desirable eradication goal of 90%, but this is non-achievable in most trials in children. Thus, it is recommended to evaluate first-line therapy at national centres, especially in areas where antimicrobial susceptibility testing is limited. This study aimed to examine the effectiveness of first-line regimen in eradicating H. pylori infection in the pediatric population in the United Arab Emirates. This retrospective study was conducted in 2017–2023, involving patients aged 1–16 years. Patients diagnosed with and treated for H. pylori infection were included, specifically those who completed 2-week treatment with documented adequate compliance. Confirmation of H. pylori eradication was done 4 weeks after the completion of antimicrobial therapy. H. pylori was detected among 447 patients, while 413 patients underwent complete treatment. Only 345 patients (77%) were evaluated for confirmed eradication via stool H. pylori antigen test (44%) or urea breath test (39%) which were the most used diagnostic modalities. Most patients (285/345; 83%) were treated with Proton Pump Inhibitor/Amoxicillin/Clarithromycin (PAC). Eradication was successful in 226 patients (65%), mostly in patients treated with the PAC regimen (193/285; 68%), compared to 20–55% eradication rates for patients treated with other regimens including metronidazole. Antibiotic regimen was the only significant predictor of eradication success (p < 0.001), with non-significant correlation with other factors as age and gender. The overall eradication rate for the first-line therapy for H. pylori falls below the recommended primary success rate for eradication (>90%). Factors influencing treatment success and adherence should be carefully considered to optimize the management of H. pylori infection in pediatric patients. Further prospective studies are warranted to validate these findings and explore additional strategies for improving treatment outcomes.